PEMBERDAYAAN MASYARAKAT MELALUI PENERAPAN BUDIDAYA IKAN HIAS AIR TAWAR DI KARANG TARUNA SINGO JOYO KABUPATEN MALANG - Ganjar Adhywirawan Sutarjo; Hany Handajani (Universitas Mataram, 2023)
Increasing the potential of the local economy can be done through the involvement of productive age communities, namely youth who are members of the youth organization. Karang Taruna is a social organization as a forum and means of development for every member of the community, growing based on social awareness and responsibility from, for and on behalf of the community, especially the village or sub-district youth generation. A youth organization that is part of the youth group